A method for preparing a supported photocatalyst and its application in pharmaceutical wastewater treatment
By modifying and grafting polymerization on the surface of nanotitanium dioxide, a supported photocatalyst is formed, which solves the problem of poor degradation and adsorption performance of nanotitanium dioxide on tetracycline, and achieves efficient adsorption and photocatalytic degradation performance, and provides pharmaceutical wastewater The tetracycline contaminants in it were excellently removed.
Patent Information
- Application Number
- CN202411067441.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-06
AI Technical Summary
Nanotitanium dioxide has poor degradation and adsorption properties on tetracycline, and it is difficult for the prior art to effectively remove tetracycline contaminants in pharmaceutical wastewater.
Modification is carried out by introducing 3,4-dihydroxybenzoic acid to the surface of nanotitanium dioxide and graft polymerization with self-polymerized monomers to form polyimide-modified nanotitanium dioxide, followed by high-temperature carbonization and potassium hydroxide pore formation Activate to prepare a supported photocatalyst.
The supported photocatalyst exhibits efficient adsorption and photocatalytic degradation properties in pharmaceutical wastewater, and the removal rate of tetracycline hydrochloride reached 99.2%, significantly improving the photocatalytic activity of nanotitanium dioxide.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, in particular to a method for preparing a supported photocatalyst and application of the supported photocatalyst in pharmaceutical wastewater treatment. Background Art
[0002] Tetracycline and its hydrochloride are a class of widely used broad-spectrum antibiotics. In the actual production process of tetracycline, the pharmaceutical wastewater produced will have residual tetracycline and other pharmaceutical pollutants, causing serious pollution. At present, the main treatment methods for pharmaceutical wastewater and medical wastewater containing tetracycline include adsorption, membrane separation, photocatalytic degradation, etc. Among them, the photocatalytic degradation method uses clean and renewable solar energy as energy, is environmentally friendly, and has high efficiency in removing pollutants.
[0003] Nano titanium dioxide is cheap and easy to obtain, green and pollution-free, and has strong photocatalytic performance. It is widely used in the field of wastewater treatment. Improving the dispersibility of nano titanium dioxide and reducing agglomeration can increase photocatalytic active sites and enhance its photocatalytic degradation performance. Developing photocatalyst carriers with high specific surface area can improve the dispersibility of the catalyst, thereby improving the photocatalytic performance. Porous carbon materials have large specific surface area, good adsorption performance, and strong electrical conductivity. They can be used as photocatalyst carriers and have wide practical applications in wastewater treatment. The patent with publication number CN114160129A discloses a method for preparing a titanium dioxide / porous carbon-supported composite photocatalyst, using carbonized coffee grounds as a porous carbon carrier and Ag-decorated nano-TiO2 as a photocatalyst. The obtained titanium dioxide / porous carbon-supported composite photocatalyst effectively adsorbs dyes in sewage and also has a significant adsorption effect on antibiotics. However, the porous carbon carrier and composite photocatalyst of the patent do not show good adsorption performance for tetracycline. Summary of the invention
[0004] The invention solves the problem that nano titanium dioxide has poor degradation and adsorption performance on tetracycline and temperature regulation.
[0005] The technical solution of the present invention is: a method for preparing a supported photocatalyst, the preparation method comprising:
[0006] Add nano-titanium dioxide to ethanol, disperse by ultrasonic, add ethanol solution containing 3,4-dihydroxybenzoic acid in nitrogen atmosphere, stir and react under light-proof, centrifuge, wash with ethanol, dry to obtain 3,4-dihydroxybenzoic acid modified nano-titanium dioxide. The reaction formula is:
[0007] Step S1, add 3,4-dihydroxybenzoic acid modified nano titanium dioxide to xylene, stir and disperse, add self-polymerizing monomer and p-toluenesulfonic acid, heat to reaction temperature, stir to carry out graft polymerization reaction, condense and reflux during reaction, centrifuge after cooling, wash with xylene and ethanol in turn, dry, and obtain polyimide modified nano titanium dioxide. The reaction formula is:
[0008] Step S2, placing the polyimide modified nano titanium dioxide into a resistance furnace for calcination and carbonization; then mixing the carbonized product with potassium hydroxide, placing it into a resistance furnace for activation and pore formation, cooling, washing, and drying to obtain a supported photocatalyst.
[0009] Furthermore, in step S1, the masses of the self-polymerizing monomer and p-toluenesulfonic acid are 1500-3000% and 4-8% of the mass of the 3,4-dihydroxybenzoic acid-modified nano-titanium dioxide, respectively.
[0010] Furthermore, in step S1, the reaction temperature is 140-145° C., and the reaction time is 5-8 h.
[0011] Furthermore, in step S2, the temperature of calcination and carbonization is 800-900°C, and the time is 2-3 hours; the temperature of activation and pore formation is 750-800°C, and the time is 1.5-2 hours.
[0012] Furthermore, in step S2, the mass of potassium hydroxide is 300-400% of the mass of the polyimide-modified nano-titanium dioxide.
[0013] Further, the preparation method of the self-polymerizing monomer is:
[0014] (1) Add toluene, methyl 3,5-diaminobenzoate and 4-hydroxyphthalic anhydride to N-methylpyrrolidone, heat to 140-150°C, perform azeotropic dehydration for 3-4 hours, then heat to 180-190°C, stir and react for 6-10 hours, cool and pour into ice water to precipitate, filter and wash with acetone, and dry to obtain an intermediate.
[0015] (2) Add the intermediate to ethanol, stir the solvent, then add 20-35% sodium hydroxide aqueous solution by mass, heat to 80-90°C, stir and react for 4-6 hours, condense and reflux during the reaction, remove ethanol by rotary evaporation, add hydrochloric acid solution to adjust the pH to 3-4, precipitate, filter and recrystallize the precipitate in ethanol to obtain a self-polymerizing monomer. The reaction formula is as follows:
[0016] Furthermore, in (1), the mass of 4-hydroxyphthalic anhydride is 195-210% of the mass of methyl 3,5-diaminobenzoate.
[0017] Furthermore, the application of supported photocatalysts in pharmaceutical wastewater treatment.
[0018] The technical effect of the present invention is as follows: the present invention uses 3,5-diaminobenzoic acid methyl ester and 4-hydroxyphthalic anhydride as raw materials, and obtains a self-polymerizing monomer containing two hydroxyl groups and one carboxyl group through an imide cyclization reaction and a hydrolysis reaction. The surface of nano titanium dioxide is further modified by using 3,4-dihydroxybenzoic acid, and a carboxyl group is introduced on the surface, which is used as a polymerization reaction site, and p-toluenesulfonic acid is used as an esterification reaction catalyst, so that the self-polymerizing monomer undergoes a graft polymerization reaction on the surface of nano titanium dioxide, thereby realizing the surface grafting modification of nano titanium dioxide by polyimide polymer, making the nano titanium dioxide uniformly dispersed in the polymer matrix, and after high-temperature carbonization, making the nano titanium dioxide uniformly distributed in the porous carbon carrier, reducing the agglomeration of nano titanium dioxide.
[0019] The polyimide polymer grafted on the surface of the modified nano titanium dioxide of the present invention contains a rigid aromatic imide ring structure, has strong carbon forming property, and can form a porous carbon material with stable structure and carbon skeleton after high-temperature calcination. After being activated by potassium hydroxide pore formation, it contains a large number of porous structures and a high specific surface area, and has good adsorption performance. The polyimide polymer contains nitrogen-containing heterocyclic rings, and after high-temperature carbonization, a nitrogen-doped structure such as pyrrole nitrogen and pyridine nitrogen is formed in the porous carbon matrix, and tetracycline hydrochloride can be adsorbed through hydrogen bonds and π-π bond interactions, so that the supported photocatalyst has a high adsorption rate and removal effect on tetracycline hydrochloride.
[0020] The nano titanium dioxide of the present invention is evenly distributed in the porous carbon carrier, reducing the agglomeration of the nano titanium dioxide. The better the dispersibility, the more photocatalytic active sites, and the better the degradation performance of tetracycline hydrochloride. At the same time, the porous carbon group doped with nitrogen has excellent conductivity, which can promote the migration of photogenerated electrons of the nano titanium dioxide, effectively inhibit the recombination of photogenerated electrons and holes, and further improve the photocatalytic activity of the nano titanium dioxide. The supported photocatalyst has a dual function of adsorption and photocatalytic degradation on tetracycline hydrochloride, thereby showing an excellent removal rate. It has broad application prospects in pharmaceutical wastewater containing tetracycline. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] Add 2 g of nano titanium dioxide to 200 mL of ethanol and disperse by ultrasonic. In a nitrogen atmosphere, add 50 mL of an ethanol solution containing 0.9 g of 3,4-dihydroxybenzoic acid. Stir and react for 18 h in the dark. Centrifuge, wash with ethanol, and dry to obtain 3,4-dihydroxybenzoic acid-modified nano titanium dioxide.
[0023] The average particle size of the nano titanium dioxide of the present invention is 40nm. The CAS registration number of 3,5-diaminobenzoic acid methyl ester is 1949-55-9. The CAS registration number of 4-hydroxyphthalic anhydride is 27550-59-0.
[0024] Example 1
[0025] (1) Add 20 mL of toluene, 4 g of methyl 3,5-diaminobenzoate, and 8.4 g of 4-hydroxyphthalic anhydride to 80 mL of N-methylpyrrolidone, heat to 140°C, and perform azeotropic dehydration for 4 h. Then heat to 190°C, stir and react for 8 h. After cooling, pour into ice water to precipitate. Filter, wash with acetone, and dry to obtain an intermediate.
[0026] (2) Add 5 g of the intermediate to 60 mL of ethanol, stir the solvent, then add 60 mL of 20% by mass sodium hydroxide aqueous solution, heat to 90°C, stir and react for 5 hours, condense and reflux during the reaction, remove ethanol by rotary evaporation, add hydrochloric acid solution to adjust the pH to 3, precipitate, filter and recrystallize the precipitate in ethanol to obtain a self-polymerizing monomer.
[0027] (3) Add 2 g of 3,4-dihydroxybenzoic acid modified nano titanium dioxide to 150 mL of xylene, stir and disperse, add 6 g of self-polymerizing monomer and 0.16 g of p-toluenesulfonic acid, heat to 140°C, stir and carry out graft polymerization reaction for 8 hours, condense and reflux during the reaction, cool and centrifuge, wash with xylene and ethanol in turn, and dry to obtain polyimide modified nano titanium dioxide.
[0028] (4) Place 10 g of polyimide-modified nano-titanium dioxide in a resistance furnace, heat it to 800°C at a heating rate of 5°C / min, and keep it warm for calcination and carbonization for 3 hours; then mix 10 g of the carbonized product with 400 g of potassium hydroxide, place it in a resistance furnace again, heat it to 800°C, keep it warm for 1.5 hours for activation and pore formation, cool it, wash it with water, and dry it to obtain a supported photocatalyst.
[0029] Example 2
[0030] (1) Add 30 mL of toluene, 4 g of methyl 3,5-diaminobenzoate, and 8.4 g of 4-hydroxyphthalic anhydride to 100 mL of N-methylpyrrolidone, heat to 140°C, and perform azeotropic dehydration for 3 h. Then heat to 190°C, stir and react for 6 h. After cooling, pour into ice water to precipitate. Filter, wash with acetone, and dry to obtain an intermediate.
[0031] (2) Add 5 g of the intermediate to 50 mL of ethanol, stir the solvent, then add 50 mL of a 20% by mass sodium hydroxide aqueous solution, heat to 80°C, stir and react for 6 hours, condense and reflux during the reaction, remove the ethanol by rotary evaporation, add hydrochloric acid solution to adjust the pH to 4, precipitate, filter and recrystallize the precipitate in ethanol to obtain a self-polymerizing monomer.
[0032] (3) Add 2 g of 3,4-dihydroxybenzoic acid modified nano titanium dioxide to 150 mL of xylene, stir and disperse, add 4.5 g of self-polymerizing monomer and 0.12 g of p-toluenesulfonic acid, heat to 140°C, stir and carry out graft polymerization reaction for 8 hours, condense and reflux during the reaction, cool and centrifuge, wash with xylene and ethanol in turn, and dry to obtain polyimide modified nano titanium dioxide.
[0033] (4) Place 10 g of polyimide-modified nano-titanium dioxide in a resistance furnace, heat it to 900°C at a heating rate of 5°C / min, and keep it warm for calcination and carbonization for 2 h; then mix 10 g of the carbonized product with 300 g of potassium hydroxide, place it in a resistance furnace again, heat it to 750°C, keep it warm for 2 h to activate and form pores, cool it, wash it with water, and dry it to obtain a supported photocatalyst.
[0034] Example 3
[0035] (1) Add 20 mL of toluene, 4 g of methyl 3,5-diaminobenzoate, and 7.8 g of 4-hydroxyphthalic anhydride to 100 mL of N-methylpyrrolidone, heat to 150°C, and perform azeotropic dehydration for 3 h. Then heat to 180°C, stir and react for 10 h. After cooling, pour into ice water to precipitate. Filter, wash with acetone, and dry to obtain an intermediate.
[0036] (2) Add 5 g of the intermediate to 60 mL of ethanol, stir the solvent, then add 60 mL of a 30% by mass sodium hydroxide aqueous solution, heat to 90°C, stir and react for 4 hours, condense and reflux during the reaction, remove the ethanol by rotary evaporation, add hydrochloric acid solution to adjust the pH to 3, precipitate, filter and recrystallize the precipitate in ethanol to obtain a self-polymerizing monomer.
[0037] (3) Add 2 g of 3,4-dihydroxybenzoic acid modified nano titanium dioxide to 120 mL of xylene, stir and disperse, add 3 g of self-polymerizing monomer and 0.08 g of p-toluenesulfonic acid, heat to 145°C, stir and carry out graft polymerization reaction for 5 hours, condense and reflux during the reaction, cool and centrifuge, wash with xylene and ethanol in turn, and dry to obtain polyimide modified nano titanium dioxide.
[0038] (4) Place 10 g of polyimide-modified nano-titanium dioxide in a resistance furnace, heat it to 850°C at a heating rate of 5°C / min, and keep it warm for calcination and carbonization for 3 h; then mix 10 g of the carbonized product with 300 g of potassium hydroxide, place it in a resistance furnace again, heat it to 750°C, keep it warm for 2 h to activate and form pores, cool it, wash it with water, and dry it to obtain a supported photocatalyst.
[0039] In Comparative Example 1, nano titanium dioxide is used as a photocatalyst.
[0040] Comparative Example 2
[0041] (1) Add 6 g of self-polymerizing monomer (same as the preparation method in Example 1) and 0.16 g of p-toluenesulfonic acid to 150 mL of xylene, raise the temperature to 140°C, stir and carry out polymerization reaction for 8 hours, condense and reflux during the reaction, cool and centrifuge, wash with xylene and ethanol in turn, and dry to obtain a polyimide polymer.
[0042] (2) Place 10 g of polyimide polymer in a resistance furnace, heat it to 800 °C at a heating rate of 5 °C / min, and keep it warm for calcination and carbonization for 3 h; then mix 10 g of the carbonized product with 400 g of potassium hydroxide, place it in a resistance furnace again, heat it to 800 °C, keep it warm for 1.5 h to activate and form pores, cool it, wash it with water, and dry it to obtain a porous carbon material as a photocatalyst.
[0043] Comparative Example 3
[0044] (1) Add 2 g of nano titanium dioxide to 150 mL of xylene, stir and disperse, add 6 g of self-polymerizing monomer (same as the preparation method in Example 1), 0.16 g of p-toluenesulfonic acid, heat to 140°C, stir and carry out polymerization reaction for 8 hours, condense and reflux during the reaction, cool and centrifuge, wash with xylene and ethanol in turn, and dry to obtain polyimide-nano titanium dioxide.
[0045] (2) Place 10 g of polyimide-nano titanium dioxide in a resistance furnace, heat it to 800°C at a heating rate of 5°C / min, and keep it warm for calcination and carbonization for 3 hours; then mix 10 g of the carbonized product with 400 g of potassium hydroxide, place it in a resistance furnace again, heat it to 800°C, keep it warm for 1.5 hours to activate and form pores, cool it, wash it with water, and dry it to obtain a supported photocatalyst.
[0046] Comparative Example 4
[0047] (1) Add 2g of nano titanium dioxide to 150mL of xylene, stir and disperse, and add 6g of 3,5-dihydroxybenzoic acid (structural formula: ), 0.16g of p-toluenesulfonic acid, heated to 140°C, stirred for graft polymerization reaction for 8h, condensed reflux during the reaction, centrifuged after cooling, washed with xylene and ethanol in turn, and dried to obtain polymer-modified nano titanium dioxide.
[0048] (2) Place 10 g of polymer-modified nano-titanium dioxide in a resistance furnace, heat it to 800 °C at a heating rate of 5 °C / min, and keep it warm for calcination and carbonization for 3 h; then mix 10 g of the carbonized product with 400 g of potassium hydroxide, place it in a resistance furnace again, heat it to 800 °C, keep it warm for activation and pore formation for 1.5 h, cool it, wash it with water, and dry it to obtain a supported photocatalyst.
[0049] Tetracycline hydrochloride was added to 1L of distilled water to prepare a tetracycline hydrochloride solution with a mass concentration of 50mg / L. Then 300-600mg of photocatalyst was added, stirred and adsorbed for 3h in the dark, centrifuged to remove the supernatant, and the tetracycline hydrochloride concentration was measured by UV-visible spectrophotometer to calculate the removal rate R.
[0050] R = (C0-C) / C0×100%. C0 is the initial concentration of tetracycline hydrochloride solution. C is the concentration of tetracycline hydrochloride in the solution after adsorption.
[0051] Table 1 Photocatalyst adsorption performance test of tetracycline hydrochloride
[0052]
[0053] After testing, the nano titanium dioxide of Comparative Example 1 had a very low removal rate of tetracycline hydrochloride under light protection and did not show adsorption performance.
[0054] Comparative Example 2 uses a polyimide polymer obtained by polymerization of a self-polymerizing monomer as a carbon precursor. After carbonization and pore activation, the obtained porous carbon material exhibits good adsorption performance for tetracycline hydrochloride and a high removal rate. The supported photocatalysts of Examples 1-3 and Comparative Example 3 use porous carbon materials as carriers of photocatalysts and exhibit good adsorption performance for tetracycline hydrochloride. This is mainly due to the fact that the polyimide polymer contains a rigid aromatic imide ring structure ( ), has a strong carbon-forming property, and after high-temperature calcination, it can form a porous carbon material with a stable structure and carbon skeleton. After potassium hydroxide pore-forming activation, it contains a large number of porous structures and a high specific surface area, and has good adsorption performance. The polyimide polymer contains nitrogen-containing heterocycles. After high-temperature carbonization, pyrrole nitrogen, pyridine nitrogen and other nitrogen-doped structures are formed in the porous carbon matrix, which can adsorb tetracycline hydrochloride through hydrogen bonds and π-π bond interactions, so that the supported photocatalyst has a high adsorption rate and removal effect on tetracycline hydrochloride.
[0055] Comparative Example 4: 3,5-dihydroxybenzoic acid is used as a self-polymerizing monomer to carry out a polymerization reaction on the surface of nano-titanium dioxide to obtain polymer-modified nano-titanium dioxide. The polymer does not contain a rigid aromatic imide ring structure, has poor carbonization, and does not contain nitrogen-doped structures such as pyrrole nitrogen and pyridine nitrogen in the porous carbon matrix after carbonization. The interaction force with tetracycline hydrochloride is low, resulting in low adsorption performance and removal rate.
[0056] Tetracycline hydrochloride was added to 1L of distilled water to prepare a tetracycline hydrochloride solution with a mass concentration of 50mg / L. Then 300-600mg of photocatalyst was added, stirred for 3h under a 300W xenon lamp, centrifuged and the supernatant was taken. The concentration of tetracycline hydrochloride was measured by UV-visible spectrophotometer, and the removal rate Q was calculated. Q=(C0-C) / C0×100%. C0 is the initial concentration of the tetracycline hydrochloride solution. C is the concentration of tetracycline hydrochloride in the solution after adsorption.
[0057] Table 2 Photocatalyst removal performance test of tetracycline hydrochloride
[0058]
[0059] As shown in Table 2, the removal rate of tetracycline hydrochloride by the supported photocatalyst of Examples 1-3 is as high as 99.2%, which is mainly attributed to the strong adsorption performance of the porous carbon carrier in the supported photocatalyst for tetracycline hydrochloride. The surface of nano-titanium dioxide is modified by 3,4-dihydroxybenzoic acid, and carboxyl groups are introduced on the surface. With them as polymerization reaction sites, self-polymerizing monomers are subjected to graft polymerization reaction on the surface of nano-titanium dioxide, thereby realizing the surface grafting modification of nano-titanium dioxide by polyimide polymer, so that nano-titanium dioxide is uniformly dispersed in the polymer matrix. After high-temperature carbonization, nano-titanium dioxide is uniformly distributed in the porous carbon carrier, reducing the agglomeration of nano-titanium dioxide. The better the dispersibility, the more photocatalytic active sites, and the better the degradation performance of tetracycline hydrochloride. At the same time, the porous carbon group doped with nitrogen has excellent conductivity, which can promote the migration of photogenerated electrons of nano-titanium dioxide, effectively inhibit the recombination of photogenerated electrons and holes, and further improve the photocatalytic activity of nano-titanium dioxide. The supported photocatalyst has dual functions of adsorption and photocatalytic degradation on tetracycline hydrochloride, thus showing excellent removal rate.
[0060] Comparative Example 1 uses nano titanium dioxide as a photocatalyst, which has poor dispersibility in water and is easy to agglomerate. It also has almost no adsorption effect on tetracycline hydrochloride and only has a photocatalytic degradation effect, resulting in a low removal rate.
[0061] The porous carbon material of Comparative Example 2 has no photocatalytic degradation performance for tetracycline hydrochloride, but only has adsorption performance, and the removal rate is low.
[0062] Compared with Example 1, the nano titanium dioxide in Comparative Example 3 has not been surface-modified with 3,4-dihydroxybenzoic acid, does not contain a carboxyl group, and cannot undergo a graft polymerization reaction with a self-polymerizing monomer, resulting in poor dispersion of the nano titanium dioxide in the polyimide polymer. After carbonization, the nano titanium dioxide is difficult to be evenly distributed in the porous carbon carrier and is prone to agglomeration. It has fewer photocatalytic active sites, poor photocatalytic degradation performance for tetracycline hydrochloride, and a removal rate lower than that of Example 1.
[0063] The porous carbon carrier of Comparative Example 4 has low interaction force and adsorption performance for tetracycline hydrochloride, and the removal rate is lower than that of Example 1 after photocatalytic degradation.
[0064] The above-mentioned embodiments only express several implementation methods of the present invention, but the implementation methods of the present invention are not limited by the above-mentioned embodiments. Any other changes made without departing from the spirit and principle of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a supported photocatalyst, characterized in that: The preparation method is: Step S1, adding 3,4-dihydroxybenzoic acid modified nano titanium dioxide to xylene, stirring and dispersing, adding self-polymerizing monomer and p-toluenesulfonic acid, heating to the reaction temperature, stirring to carry out graft polymerization reaction, condensing and refluxing during the reaction, centrifuging after cooling, washing with xylene and ethanol in turn, and drying to obtain polyimide modified nano titanium dioxide; The structural formula of the self-polymerizing monomer is as follows: ; Step S2, placing the polyimide modified nano titanium dioxide into a resistance furnace for calcination and carbonization; then mixing the carbonized product with potassium hydroxide, placing it into a resistance furnace for activation and pore formation, cooling, washing, and drying to obtain a supported photocatalyst.
2. The method for preparing a supported photocatalyst according to claim 1, characterized in that: In the step S1, the masses of the self-polymerizing monomer and p-toluenesulfonic acid are 1500-3000% and 4-8% of the mass of the 3,4-dihydroxybenzoic acid-modified nano-titanium dioxide, respectively.
3. The method for preparing a supported photocatalyst according to claim 1, characterized in that: In step S1, the reaction temperature is 140-145° C., and the reaction time is 5-8 hours.
4. The method for preparing a supported photocatalyst according to claim 1, characterized in that: In the step S2, the temperature of calcination and carbonization is 800-900°C and the time is 2-3 hours; the temperature of activation and pore formation is 750-800°C and the time is 1.5-2 hours.
5. The method for preparing a supported photocatalyst according to claim 1, characterized in that: The mass of potassium hydroxide in step S2 is 300-400% of the mass of polyimide-modified nano-titanium dioxide.
6. The method for preparing a supported photocatalyst according to claim 2, characterized in that: The preparation method of the self-polymerizing monomer is: (1) Add toluene, methyl 3,5-diaminobenzoate and 4-hydroxyphthalic anhydride to N-methylpyrrolidone, heat to 140-150°C, perform azeotropic dehydration for 3-4 hours, then heat to 180-190°C, stir and react for 6-10 hours, cool and pour into ice water to precipitate, filter, wash and dry to obtain an intermediate; (2) Add the intermediate to ethanol, stir the solvent and then add aqueous sodium hydroxide solution, heat to 80-90°C, stir and react for 4-6 hours, condense and reflux during the reaction, remove ethanol by rotary evaporation, add hydrochloric acid solution to adjust the pH to 3-4, precipitate, filter and recrystallize to obtain a self-polymerizing monomer.
7. The method for preparing a supported photocatalyst according to claim 6, characterized in that: In the above (1), the mass of 4-hydroxyphthalic anhydride is 195-210% of the mass of 3,5-diaminobenzoic acid methyl ester.
8. The method for preparing a supported photocatalyst according to claim 6, characterized in that: In the above (2), the mass fraction of the sodium hydroxide aqueous solution is 20-35%.
9. The method for preparing a supported photocatalyst according to claim 6, characterized in that: The preparation method of the 3,4-dihydroxybenzoic acid modified nano titanium dioxide is as follows: adding nano titanium dioxide to ethanol, ultrasonically dispersing, adding an ethanol solution containing 3,4-dihydroxybenzoic acid in a nitrogen atmosphere, stirring and reacting in the dark, centrifugation, ethanol washing, and drying to obtain the 3,4-dihydroxybenzoic acid modified nano titanium dioxide.
10. Use of the supported photocatalyst obtained by the preparation method according to any one of claims 1 to 9 in the treatment of pharmaceutical wastewater.
Citation Information
Patent Citations
Preparation method of titanium dioxide / porous carbon supported composite photocatalyst
CN114160129A
Method for photocatalytic degradation of antibiotics
CN111974373A
Preparation method of TiO2-polyethyleneimine-graphene composite adsorbing and degrading material
CN112495354A
Cited By
Preparation method and application of foam cellulose loaded sulfur-doped carbon nitride photocatalyst
CN120885265A